Effects of swissball training in combination with ballistic and PNF stretching on coordinative abilities among adolescents boys (International Journal of Food and Nutritional Sciences, 2022)
This research aimed to investigate the effects of Swiss ball training in combination with ballistic and PNF stretching on coordinative abilities among adolescent boys. The study involved 60 healthy male students aged between 14 to 16 years old from a high school in the city of [Kashmir]. Participants were randomly assigned to three groups: Swiss ball training with ballistic and PNF stretching (SBP), Swiss ball training only (SB), and control group (CG). All groups were assessed for their coordinative abilities using the Körperkoordinationstest für Kinder (KTK) before and after the intervention. Results showed that the SBP group had significant improvements in all KTK subtests compared to the SB and CG groups. These findings suggest that Swiss ball training in combination with ballistic and PNF stretching could be an effective intervention to enhance coordinative abilities among adolescent boys.